Endocrine emergencies. Issue 3 (March 2020) - Mishra, Apurva; Quinn, Marc
Endocrine emergencies represent a small group of conditions, where the presentation is related to either a relative lack or excess of hormones. They may present with non-specific features, which can make them difficult to diagnose. Endocrine emergencies are commonly treated in a hospital setting. Having a high degree of suspicion and awareness of the presentation can lead to early diagnosis and prompt management. This article focuses on the epidemiology, common presentation, risk factors, investigation and management of diabetic ketoacidosis, hyperosmolar hyperglycaemic state, hypoglycaemia, thyroid storm, myxoedema crisis, adrenal insufficiency, hypercalcaemia, phaeochromocytoma and acute pituitary failure.